Representasi Anime One Piece Dalam Menumbuhkan Sikap Kalyāṇamitta - Alta Defano Gautama; Wina Dhamayanti (Jounal Nyanadassana, 2026)
This study aims to examine the representation of kalyāṇamitta (good friend) values ​​in the One Piece anime and its potential as a character learning medium in the context of Buddhist education. Anime as a form of popular culture has a strong appeal to the younger generation and can be an effective means of conveying ethical and spiritual values. Through a literature study method approach, this study analyzes the characters and storylines in One Piece that reflect kalyāṇamitta attitudes, such as loyalty, sacrifice, and solidarity. The results of the analysis show that the friendship values ​​displayed in the anime are in line with Buddhist teachings on kalyāṇamitta, and can be an inspiration in the formation of the moral character of Buddhist teenagers. Thus, One Piece is not only entertainment but also has educational potential in supporting the learning of goodness and spiritual values ​​in everyday life.